Managing tooth pain in general practice - Koh, Sky Wei Chee (Singapore Med J, 2019)
Tooth pain is a common presentation in primary care, with 32.4% of Singaporeans experiencing pain from dental caries in their lifetime. Some systemic conditions can have oral presentations, and oral conditions may be associated with chronic disease. A good history and examination is key in delineating odontogenic from non-odontogenic causes of tooth pain. Primary care physicians should accurately diagnose and assess common dental conditions and make appropriate referrals to the dentist. Common non-odontogenic causes of orofacial pain can be mostly managed in primary care, but important diagnoses such as acute coronary syndrome, peritonsillar abscess and temporal arteritis must not be missed. Ibuprofen has been shown to be effacious, safe and cost-effective in managing odontogenic pain. Antibiotics are indicated when there is systemic or local spread of dental infection. Without evidence of spread, antibiotics have not been shown to reduce pain or prevent subsequent dental infections.